PEMETAAN POTENSI WISATA HALAL DI KABUPATEN SUMENEP, JAWA TIMUR, INDONESIA - Kurniawan, Fredy; Soeprijanto, Adi; Guntur, Harus Laksana; Wardhana, Mahendra; Abadi, Imam; -, Sayyida (Dinar Jurnal Ekonomi dan Keuangan Islam, 2018)
Tourism activities are one thing for supporting regions and the countrys economic development, through foreign exchange, tax revenues, and other levies. Tourism activities in one area can increase employment, accelerate the construction of facilities and infrastructure. Tourism also be able to introduce the local production goods for local and foreign tourists. Recently, the Muslim community is the largest community in the world and Indonesia is one of the countries with the most Muslim population. Seeing this opportunity, the Indonesian government in 2012 began for introducing halal tourism in Indonesia. Sumenep, East Java, Indonesia has a variety of tourism potential that can be developed into halal tourism. This study has been mapped all potential for halal tourism in Sumenep, East Java, Indonesia. The potential of halal tourism in Sumenep which has been successfully mapped includes object of food, beach tourism, traditional weapon (keris) tours, centers of batik Sumenep, religious tours, historical tours and natural tours. Hotel and hostelry was also available so that the tourist can plan their vacation in the desire time. Transportation between tourist attractions can also be accessed easily. All tourism objects are includes the criteria of Halal tourism. It can be summarized as Sumenep Halal tour package. This potential was also supported by the religious culture of Sumenep people. This mapping will make it easier for Muslim tourists in particular to access halal tourism in Sumenep, East Java, Indonesia.